A risk preference model for teaching resource allocation based on functional link fuzzy neural network algorithm classifier. (2nd September 2019) - Tongpeng, Wei; Li, Chen
The volleyball teaching resource allocation model based on the functional link fuzzy neural network algorithm is proposed to improve the effectiveness of volleyball teaching resource allocation in course arrangement process. Firstly, the risk preference allocation model for volleyball teaching resource allocation is designed based on the functional link fuzzy neural network algorithm classifier, the risk is divided into existing and non-existing risk preferences and the functional link fuzzy neural network algorithm classifier is used to achieve the training and data optimisation of volleyball teaching resource allocation data set; secondly, considering that the functional link fuzzy neural network algorithm classifier may break down in volleyball teaching resource allocation prediction process, the functional link fuzzy neural network algorithm is used to achieve optimisation of volleyball teaching resource allocation process; finally, the stimulation research on the volleyball teaching resource allocation model example shows that the more reasonable volleyball teaching resource allocation model can be obtained by the proposed algorithm, reflecting the effectiveness of algorithm.